Antibiotic Prophylaxis of Infective Endocarditis: From the History of the Concept to Modern Recommendations (Review) - G. G. Taradin; E. Yu. Ponomareva; G. A. Ignatenko; N. T. Vatutin; B. D. Prendergast (Архивъ внутренней медицины)
The presented review highlights current understandings of prophylaxis for infective endocarditis (IE). The historic aspects of the concept development of antibacterial prophylaxis (ABP) for IE, the main approaches and the rationale for changing the principles of ABP in recent years are described. There are detailed clarifications of published international and national recommendations, in particular, of European Society of Cardiology, National Institute for Health and Clinical Excellence, American Heart Association/American College of Cardiology and Japanese Circulation Society. The critical estimation of earlier adopted international guidelines with analysis of influence of partial or absolute ABP restrictions on the incidence of IE and its complications including fatality rate are presented.